Sleep Habits in Special Needs Students in Elementary School: A Cross-Sectional Study - Saideh Sadat Mortazavi; Zahra Mortazavi; Hamed Jahan; Hassan Ahmadinia; Amir Seyedahmadi; Nasrin Gohari (مجله پژوهش در علوم توانبخشی, 2021)
Introduction: Sleep is one of the most vital needs and a factor influencing the academic performance of students. Sleep habits are formed before adolescence and are maintained throughout life. This study aims to investigate the sleep habits of students with special needs in the elementary schools of Hamadan, Iran, from the parents' point of view.Materials and Methods: In this cross-sectioninal descriptive-analytical study, 102 students with special needs aged 7-13 years old were selected throughthe convenience sampling method in Hamadan City, 2021. Data were collected by demographic information questionnaire and the Children's Sleep Habits Questionnaire (CSHQ) with the self-report method (by the mother). Data were analyzed with descriptive statistics methods, t-tests, Mann-Whitney U, and Kruskal-Wallis test in SPSS software. Level of significance was considered less than 0.05.Results: The mean score of the students' sleep habits was 76.87 ± 17.24 in girls and 73.90 ± 17.99 in boys. Sleep duration in girls was 9.42 ± 1.40 hours and in boys 9.53 ± 1.22 hours. Disturbance in sleep habits was reported more in students with cerebral palsy than other groups.Conclusion: The findings of this study showed that sleep habit disorders were prevalent in students with cerebral palsy, autism, Down syndrome, low vision, hearing impairment, and motor sensory disabilities.